Is Early Start a Better Start? Evaluating California State University's Early Start Remediation Policy - Michal Kurlaender; Lester Lusher; Matthew Case (Institute of Labor Economics (IZA), 2019)
Remediation has long been a costly way to address the misalignment between K-12 and higher education. In 2011, the California State University (CSU), the nation's largest public four-year university system, enacted Early Start, requiring students needing remediation to enroll in such courses in the summer before their freshmen year. We estimate the impact of Early Start summer remediation relative to both traditional fall remediation and relative to no remediation at all. Our results suggest Early Start summer remediation has not improved student performance or persistence relative to either alternative. As many states move away from remedial courses altogether, there is continued need for both innovation and for evidence in policy and practice to improve college readiness and success.
Keywords: I20; I23; I28; 330; higher education; remediation; state policy